A Double Edged Sword? Improvements in Economic Conditions over a Decade in India Led to Declines in Undernutrition as Well as Increases in Overweight among Adolescents and Women. Issue 2 (16th October 2019) - Young, Melissa F; Nguyen, Phuong; Tran, Lan Mai; Avula, Rasmi; Menon, Purnima
ABSTRACT: Background: India is facing a dual burden of undernutrition and overweight/obesity, and there are gaps in our understanding of the driving factors over time. Objective: This study examined the national and state trends for BMI and identified the determinants of underweight and overweight/obesity among adolescent girls and women. Methods: We used India's National Family Health Surveys data collected in 2005–2006 ( n  = 110, 887) and 2015–2016 ( n  = 645, 193). We applied multiple regression and decomposition analysis to assess determinants of underweight (BMI z score <  −1 SD; <18.5 kg/m 2 ) and overweight/obesity (BMI z score >1 SD; ≥25 kg/m 2 ). Results: Over the past decade, the prevalence of underweight decreased (43% to 38% and 33% to 19%) and the prevalence of overweight/obesity increased (3% to 5% and 15% to 24%), among adolescents and women, respectively, with high heterogeneity across states. Factors associated with a lower prevalence of underweight among women included higher socioeconomic status (SES) (OR: 0.35; 95% CI: 0.31, 0.41), urban residence (OR: 0.49; 95% CI: 0.45, 0.54), improved diet diversity (OR: 0.75; 95% CI: 0.69, 0.82), and latrine use (OR: 0.76; 95% CI: 0.70, 0.82). Higher education levels, decision-making, and ownership of money were also associated with a lower prevalence of underweight. Factors positively associated with overweight/obesity among women included SES (OR: 3.24; 95% CI: 2.81, 3.73), urban residence (OR: 2.23; 95% CI: 2.05, 2.42), diet diversity (OR: 1.21; 95% CI: 1.10, 1.32), latrine use (OR: 1.31; 95% CI: 1.21, 1.43), and education (OR: 1.39; 95% CI: 1.24, 1.55). Adolescents shared similar determinants to women. Overall, SES was a key driver of changes in women's BMI, explaining 29% of the reduction in undernutrition and 46% of the increase in overweight/obesity. Conclusions: Despite overall declines, regional and age disparities remain in the overall burden of underweight and the increases in overweight/obesity are concerning. The identified divergent risk factors (SES, residence, diet, education) highlight that simply improving economic status will not ensure healthy BMI status for women and girls. Balanced multidisciplinary approaches are needed to address both undernutrition and overweight.